The COST Manual of Laboratory Animal Care and Use Refinement, Reduction, and Research - Howard, Bryan (Taylor & Francis, 2010)
Judge Your Practices Against This Benchmark Manual COST Action B-24 established four working groups to research and discuss issues relevant to laboratory animal science. These included the housing of animals, environmental needs, refinement of procedures, genetically modified animals, and cost-benefit analysis. Based on the groups' findings, The COST Manual of Laboratory Animal Care and Use: Refinement, Reduction, and Research provides a consensual European view of best practices for individuals and institutions caring for and working with laboratory animals. What is COST? COST (European Cooperation in Science and Technology) is an intergovernmental initiative that promotes coordination of nationally funded science and research at a European level. This book focuses on reduction and refinement strategies and includes insightful contributions from 44 experts drawn from various EU countries. Addressing only the most commonly used mammalian species-rats, mice, and rabbits-each chapter of the book follows a similar structure: Objectives outline the breadth of the chapter's coverage Key Factors summarize the central issues that underpin good practice Questions Unresolved close each chapter, identifying areas of uncertainty and prompting investigations directed at advancing knowledge and application within relevant fields The COST Manual of Laboratory Animal Care and Use: Refinement, Reduction, and Research is the reference sure to be found in the lab coats of those responsible for the care and welfare of animals and those overseeing and conducting activities related to the use of animals for scientific purposes.